Analysis of biological properties of 1,2,4-triazole-containing compounds (literature review) - Khilkovets, A. V.; Parchenko, V. V.; Хільковець, А. В.; Парченко, Володимир Володимирович; Хильковец, А. В.; Парченко, В. В. (Запорізький державний медичний університет, 2022)
In the latest conditions of development and formation of the pharmaceutical industry, the introduction of new synthetic medicines requires continuous monitoring of the quality and safety of their use. For many years, synthetic drugs have remained an essential tool in the prevention and control of diseases of various etiologies. Among the synthetic class of substances, first of all, those that are low-toxic, safe, and effective deserve attention. In recent decades scientific publications prove the prospects of searching for new biologically active compounds among derivatives of 1,2,4-triazoles with fragments of various heterocyclic systems. Scientists claim that the combination of several structural fragments of heterocycles in one molecule leads to the emergence of new types of biological action, and sometimes to an increase in known pharmacological effects. At the same time, the synthesized compounds belong to the class of low-toxic or practically non-toxic substances. The aim of our work is to analyze foreign and native sources on the biological activity of 1,2,4-triazole derivatives. Conclusions. Among these derivatives, molecules that exhibit broad antifungal and antimicrobial activity, antitubercular, antiviral, actoprotective, antihypoxic, analgesic effects, etc. were found. After analyzing the known data, a number of «structure-action» regularities were established. The obtained results will be useful for further research work of scientists. У сучасних умовах розвитку і становлення фармацевтичної промисловості впровадження нових синтетичних лікарських засобів потребує постійного контролю якості та безпеки їх використання. Протягом багатьох років синтетичні ліки залишаються суттєвим інструментом щодо профілактики та боротьби з хворобами різної етіології. Серед синтетичного класу речовин передусім заслуговують на увагу ті, що є малотоксичними, безпечними й ефективними. Наукові публікації в останні десятиліття показують перспективність пошуку нових біологічно активних сполук серед похідних 1,2,4-тріазолів із фрагментами різних гетероциклічних систем. Учені стверджують, що поєднання декількох структурних фрагментів гетероциклів в одній молекулі призводить до появи нових видів біологічної дії, інколи і до посилення відомих фармакологічних ефектів. До того ж синтезовані сполуки належать до класу малотоксичних чи практично нетоксичних речовин. Мета роботи – аналіз закордонних і вітчизняних джерел щодо біологічної активності 1,2,4-тріазолпохідних. Висновки. Серед зазначених похідних виявлено молекули, які проявляють широку протигрибкову та протимікробну активність, протитуберкульозну, противірусну, актопротекторну, антигіпоксичну, анальгетичну дію тощо. Проаналізувавши відомі дані, встановлено низку закономірностей «будова – дія». Результати будуть корисними для подальшої науково-дослідної роботи вчених. В новейших условиях развития и становления фармацевтической промышленности внедрение новых синтетических лекарственных средств требует постоянного контроля качества и безопасности их использования. В течение многих лет синтетические лекарства остаются существенным инструментом в профилактике и борьбе с болезнями разной этиологии. Среди синтетического класса веществ прежде всего заслуживают внимания малотоксичные, безопасные и эффективные. Научные публикации за последние десятилетия доказывают перспективность поиска новых биологически активных соединений среди производных 1,2,4-триазолов с фрагментами различных гетероциклических систем. Учёные утверждают, что сочетание нескольких структурных фрагментов гетероциклов в одной молекуле приводит к появлению новых видов биологического действия, а иногда и к усилению известных фармакологических эффектов. При этом синтезированные соединения относятся к классу малотоксичных или практически нетоксичных веществ. Цель работы – анализ зарубежных и отечественных источников, касающихся биологической активности 1,2,4-триазолпроизводных. Выводы. Среди указанных производных найдены молекулы, которые проявляют широкую противогрибковую и противомикробную активность, противотуберкулезное, противовирусное, актопротекторное, антигипоксическое, анальгетическое действие и т. д. Проанализировав известные данные, установили ряд закономерностей «строение – действие». Результаты будут полезны для дальнейшей научно-исследовательской работы учёных.
Аналіз біологічних властивостей 1,2,4-тріазолвмісних сполук (огляд літератури)
Анализ биологических свойств 1,2,4-триазолсодержащих соединений (обзор литературы)
Khilkovets A. V. - ORCID ID: 0000-0001-7401-9458; Parchenko V. V. - RCID ID: 0000-0002-2283-1695.
Keywords: 1,2,4-triazole; biological properties; activity; 1,2,4-тріазол; біологічні властивості; активність; 1,2,4-триазол; биологические свойства; активность